Getting Ahead in Singapore: How Neighborhoods, Gender, and Ethnicity Affect Enrollment into Elite Schools. Issue 2 (April 2019) - Chua, Vincent; Swee, Eik Leong; Wellman, Barry
Is education the social leveler it promises to be? Nowhere is this question better addressed than in Singapore, the emblematic modern-day meritocracy where education has long been hailed as the most important ticket to elite status. In particular, what accounts for gender and ethnic gaps in enrollment into Singapore's elite junior colleges—the key sorters in the country's education system? We consider how the wealth of neighborhoods has combined with the elite status of schools to affect the social mobility of gender and ethnic groups. Analyzing data from 40 years of junior college yearbooks (1971–2010), we find persistent differences in educational opportunity. Women and Malays have historically experienced inequality in Singapore, and their student routes to becoming elites differ markedly. For female students, attending an elite junior college in a wealthy neighborhood is associated with wealthy neighborhoods that have a disproportionate number of elite girls' secondary schools that feed into the junior colleges. By contrast, for Malays, not attending an elite junior college in a wealthy neighborhood has more to do with wealthy neighborhoods underrepresenting Malays in demographic composition. Elite families thus now include better educated women as well as men, yet Malays still rarely become better educated elites. These results underscore the need to carefully map the complex associations and mechanisms between gender and ethnic categorizations, the status of schools, and the characteristics of neighborhoods.